Desmin variants: Trigger for cardiac arrhythmias? - Su, Wei; van Wijk, Stan W.; Brundel, Bianca J. J. M. (Frontiers in Cell and Developmental Biology, 2022)
Desmin is a classical type III intermediate filament protein encoded by the DES gene. Desmin is abundantly expressed in cardiac, skeletal, and smooth muscle cells. In these cells, desmin interconnects several protein-protein complexes that cover cell-cell contact, intracellular organelles such as mitochondria and the nucleus, and the cytoskeletal network. The extra- and intracellular localization of the desmin network reveals its crucial role in maintaining the structural and mechanical integrity of cells. In the heart, desmin is present in specific structures of the cardiac conduction system including the sinoatrial node, atrioventricular node, and His-Purkinje system. Genetic variations and loss of desmin drive a variety of conditions, so-called desminopathies, which include desmin‐related cardiomyopathy, conduction system-related atrial and ventricular arrhythmias, and sudden cardiac death. The severe cardiac disease outcomes emphasize the clinical need to understand the molecular and cellular role of desmin driving desminopathies. As the role of desmin in cardiomyopathies has been discussed thoroughly, the current review is focused on the role of desmin impairment as a trigger for cardiac arrhythmias. Here, the molecular and cellular mechanisms of desmin to underlie a healthy cardiac conduction system and how impaired desmin triggers cardiac arrhythmias, including atrial fibrillation, are discussed. Furthermore, an overview of available (genetic) desmin model systems for experimental cardiac arrhythmia studies is provided. Finally, potential implications for future clinical treatments of cardiac arrhythmias directed at desmin are highlighted.